Sequential Evaluation of Dogs Naturally Infected with Ehrlichia canis, Ehrlichia chaffeensis, Ehrlichia equi, Ehrlichia ewingii, or Bartonella vinsonii - Breitschwerdt, Edward B. (American Society for Microbiology, 1998)
Historically, disease manifestations in dogs seroreactive to Ehrlichia canis antigens by indirect immunofluorescent antibody testing have been attributed to infection with either E. canis or Ehrlichia ewingii. A 1996 study by Dawson and colleagues provided PCR evidence that healthy dogs from southeastern Virginia could be naturally infected with Ehrlichia chaffeensis. This observation stimulated us to determine which Ehrlichia spp. infected sick dogs that were referred to our hospital from the same region. Based upon PCR amplification with species-specific primers, sick dogs seroreactive to E. canis antigens were determined to be infected with four Ehrlichia species: E. canis, E. chaffeensis, E. equi, and E. ewingii. Coinfection with three Ehrlichia species (E. canis, E. ewingii, and E. equi) was documented for one dog. An additional canine pathogen presumed to be tick transmitted, Bartonella vinsonii subsp. berkhoffii, was identified in 7 of 12 dogs. Importantly, our results indicate that in naturally infected dogs, E. chaffeensis can cause severe disease manifestations that are clinically and serologically indistinguishable from disease manifestations of E. canis or E. ewingii. In addition, our findings support the efficacy of doxycycline for treatment of E. canis, E. equi, and E. ewingii infections but indicate that, based upon the persistence of E. chaffeensis DNA for 1 year following treatment, E. chaffeensis infection in dogs may be more refractory to doxycycline treatment. Undetected coinfection with Bartonella may also complicate the evaluation of treatment efficacy while resulting in disease manifestations that mimic ehrlichiosis.